2021
DOI: 10.3389/fimmu.2021.736269
|View full text |Cite
|
Sign up to set email alerts
|

GITR Promotes the Polarization of TFH-Like Cells in Helicobacter pylori-Positive Gastritis

Abstract: Gastric CD4+T cells contribute to Helicobacter pylori (H. pylori)-induced gastritis by amplifying mucosal inflammation and exacerbating mucosal injuries. However, the pathogenic CD4+ T cell subset involved in gastritis and the potential regulators are still unclear. Here we identified an IL-21-producing gastric CD4+T cell subset, which exhibited tissue-resident CXCR5−BTLA−PD-1hi TFH-like phenotype in H. pylori-positive gastritis patients. Meanwhile, we identified glucocorticoid-induced tumor necrosis factor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Importantly, we show the strong positive correlation between elevation of circulating TFHs and desialylated platelets, supporting TFHs as a critical mediator in synergy to promote platelet desialylation. A recent study found that H. Pylori infection may lead to the upregulation of TFHs in gastritis patients ( 41 ), and several recent reports revealed an association between H. Pylori infection and the incidence of ITP ( 42 44 ). Hence, we speculate that H. Pylori may be related to the abnormally elevated TFHs in the infected individuals with ITP in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we show the strong positive correlation between elevation of circulating TFHs and desialylated platelets, supporting TFHs as a critical mediator in synergy to promote platelet desialylation. A recent study found that H. Pylori infection may lead to the upregulation of TFHs in gastritis patients ( 41 ), and several recent reports revealed an association between H. Pylori infection and the incidence of ITP ( 42 44 ). Hence, we speculate that H. Pylori may be related to the abnormally elevated TFHs in the infected individuals with ITP in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The real-time PCR was performed as previously described [ 31 ]. Total RNA was isolated using TRIzol reagent (Invitrogen, USA) according to the manufacturer's recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…The increase of CD4 + T lymphocyte level has a close relationship with the injury of gastric mucosa caused by Hp infection. 15 Moreover, CD4+T cells may function significantly in regulating or inhibiting CD8 + T cells, and CD8 + T cells may mediate more serious diseases in the absence of CD4 + T cells. 16 There would be obvious increase in the levels of CD4 + and CD8 + T lymphocytes in peripheral blood of children with Hp infection.…”
Section: Discussionmentioning
confidence: 99%